The use of numerical simulation for the evaluation of special transparent glass resistance. (September 2018) - Binar, Tomáš; Švarc, Jiří; Vyroubal, Petr; Kazda, Tomáš; Rolc, Stanislav; Dvořák, Aleš; Dostál, Petr
Abstract: The paper is concerned with the use of numerical simulation for the evaluation of projectile interaction with an assembly composed of multiple materials (transparent armour). For the purpose of assessing the reliability of theoretical numerical models, LS-Dyna explicit solver was employed allowing the evaluation of the projectile interaction effect on the experiment material tested. The material parameters for the numerical simulations were obtained at the temperature of 20 °C. The research objective was to evaluate the projectile interaction with an assembly composed of multiple materials at the temperatures of −32 °C and 55 °C, and to evaluate the scope of damage, the delamination of individual layers of transparent armour and the depth of projectile penetration at Protection Level 2 [PARTIAL] (7.62 mm × 39 API BZ) a Level 3 (only projectile 7.62 mm × 54R B32 API). Highlights: The data from the simulation of the projectile shot to transparent armour in an DINGO vehicle correspond with the simulation. Impact of the extreme temperature stress on the depth of penetration was demonstrated by measurement and simulation. The mechanism of deformation of the individual layers of the armour affected by extreme temperatures stress was described.